Development and validation of a prognostic score for TIPS placement in patients with viral hepatitis cirrhosis-related portal hypertension: a multi-center retrospective study - Que, Zenglong; Wu, Mingsong; Lai, Shujie; Wang, Lei; Mu, Zhiyong; Yang, Jinhui; Xiong, Wei; Hu, Hong; Liu, Aimin; An, Xuan; Yu, Haodong; Cao, Qin; et al. (Frontiers in Medicine, 2024)
Introduction: There is no established scoring model focus on viral hepatitis patients to predict the prognosis after transjugular intrahepatic portosystemic shunt (TIPS). We aimed to develop and validate a novel model based on the largest cohort for better prediction of both short-term (1 year) and long-term (3 years) postoperative prognosis after TIPS in viral hepatitis cirrhosis-related portal hypertension patients. Methods: A total of 925 viral hepatitis cirrhosis-related portal hypertension patients underwent TIPS from nine hospitals were divided into the training and external validation cohorts. A novel Viral-associated Index of Post-TIPS score (VIPs) model was built after performing cox regression. We compared it with five previous models including Child-Pugh, MELD, ALBI, CCG and FIPS. Furthermore, Using X-tile software to stratify patients into low-medium-high risk groups. Results: The VIP score model including age, ascites, albumin, prothrombin time, total bilirubin, and sodium for post-TIPS prognosis prediction. The model demonstrated a satisfying predictive efficiency in both discrimination and calibration, with an area under the curve of 0.781/0.774 (1-year/3-year) in the training cohort and 0.771/0.775 (1-year/3-year) in the external validation cohort, respectively. Discussion: We firstly developed and external validated a novel VIPs model for better prediction of both short-term and long-term postoperative prognosis after TIPS in Chinese patients with viral hepatitis cirrhosis-related portal hypertension.